Presidents and policy-making: has Brazil's CCT-led anti-poverty agenda gone far enough?*. (4th May 2017) - Fenwick, Tracy B.
ABSTRACT: In order to identify the causal mechanisms (rational learning, adaptation, and innovation) driving changes in the area of anti-poverty policy in Brazil, this article traces the micro-level decision-making processes across three presidents. It begins by laying out the politics of conditional cash transfers (CCTs) in Brazil and presidential usage of this targeted social policy instrument since the 1990s. In contrast to previous presidents, President Dilma Rousseff's decisions did not enable her rationally intended policy agenda. Why? The President him or herself is privileged as the central actor whose decision-making processes impact policy development and its subsequent performance. I will argue that prior to the most recent changes under Dilma, was the demise of CCTs being 'good enough' from a policy perspective. The major challenge for any president in Brazil remains low levels of political and societal consensus over the kind of social reforms required to end the intergenerational transmission of poverty in Brazil; a policy dilemma confounded by the absence of a single unifying institutional actor and the extent of power diffusion in Brazilian federalism.